Equivalence

In Chapter 5, we saw DeMorgan’s laws for quantifiers – that if we have some domain, and if P(x) is a predicate for individuals in that domain, then the following statements are equivalent:

  • ¬(∃ x P(x)) is equivalent to ∀ x ¬P(x)
  • ¬(∀ x P(x)) is equivalent to ∃ x ¬P(x)

The process of proving that two predicate logic statements are equivalent is the same as it was in propositional logic – we must prove the second proposition using the first as a premise, and we must prove the first given the second as a premise.

Example - how to prove equivalence

For example, to prove that ¬(∃ x P(x)) is equivalent to ∀ x ¬P(x), we must prove the sequents:

¬(∃ x P(x)) ⊢ ∀ x ¬P(x)

and

∀ x ¬P(x) ⊢ ¬(∃ x P(x))

We prove both directions below:

¬(∃ x P(x)) ⊢ ∀ x ¬P(x)
{
    1. ¬(∃ x P(x))              premise
    2. {
        3. a
        4. {
            5. P(a)             assume
            6. ∃ x P(x)         ∃i 5 a
            7. ⊥                ¬e 6 1
        }
        8. ¬P(a)                ¬i 4
    }
    9. ∀ x ¬P(x)                ∀i 2
}

and

∀ x ¬P(x) ⊢ ¬(∃ x P(x))
{
    1. ∀ x ¬P(x)                premise
    2. {
        3. ∃ x P(x)             assume
        4. {
            5. a P(a)           assume
            6. ¬P(a)            ∀i 1 a
            7. ⊥                ¬e 5 6
        }
        8. ⊥                    ∃e 3 4
    }
    9. ¬(∃ x P(x))              ¬i 2
}

More extensive list of equivalences

Here is a more extensive list of equivalences in predicate logic. The remaining proofs are left as exercises for the reader:

  • ¬(∃ x P(x)) is equivalent to ∀ x ¬P(x)
  • ¬(∀ x P(x)) is equivalent to ∃ x ¬P(x)
  • ∀ x (P(x) → ¬Q(x)) is equivalent to ¬(∃ x P(x) ∧ Q(x))
  • ∀ x ∀ y P(x, y) is equivalent to ∀ y ∀ x P(x, y)
  • ∃ x ∃ y P(x, y) is equivalent to ∃ y ∃ x P(x, y)
  • Q ∧ (∀ x P(x)) is equivalent to ∀ x (Q ∧ P(x)) (where x does not appear in Q)
  • Q v (∀ x P(x)) is equivalent to ∀ x (Q V P(x)) (where x does not appear in Q)
  • Q ∧ (∃ x P(x)) is equivalent to ∃ x (Q ∧ P(x)) (where x does not appear in Q)
  • Q V (∃ x P(x)) is equivalent to ∃ x (Q V P(x)) (where x does not appear in Q)